2021
DOI: 10.6065/apem.2040220.110
|View full text |Cite
|
Sign up to set email alerts
|

Clinical findings influencing time to menarche post gonadotropin-releasing hormone agonist therapy in central precocious puberty

Abstract: This study aimed to evaluate the time interval to menarche after gonadotropin-releasing hormone agonist (GnRHa) treatment in females with central precocious puberty (CPP) and identify factors contributing to timing of menarche.Methods:We retrospectively reviewed medical records of 39 females with CPP who reached menarche after GnRHa treatment (leuprolide or histrelin). CPP diagnostic criteria were: breast development <8 years, pubertal luteinizing hormone and/or estradiol concentrations, and bone age advancem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Studies [ 19 ] have shown that precocious puberty is correlated with obesity, and obesity affects female hormone levels throughout preadolescence, adolescence, and adulthood. Other animal experiments [ 20 ] have shown that obesity caused by high fat diet is an important factor in inducing sexual maturity in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Studies [ 19 ] have shown that precocious puberty is correlated with obesity, and obesity affects female hormone levels throughout preadolescence, adolescence, and adulthood. Other animal experiments [ 20 ] have shown that obesity caused by high fat diet is an important factor in inducing sexual maturity in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment in girls could be stopped at 10–11 years of age, to have menarche occurring near their peers 14. Pubertal progression usually occurs within months after the therapy discontinuation, with a mean time to menarche of 18 months 23–25. The best height outcomes are obtained when GnRH agonists are stopped when the bone age is between 12 and 12.5 years in girls, and between 13 and 13.5 years in boys 21 26…”
Section: When Should the Therapy Be Withdrawn?mentioning
confidence: 99%
“…38,67,68) In girls with CPP, menarche is predicted after an average of 12 to 18 months after the completion of treatment and may begin after a few months or be delayed as long as 2 years. 58,69) It is recommended that the discontinuation of GnRH agonist treatment be decided after providing information about the FAH and pubertal progression to the guardians and patients, as well as an achievement of appropriate BA or CA.…”
Section: Do Strong)mentioning
confidence: 99%
“…In general, the longer the treatment period, the higher FAH, but in girls who are treated with GnRH agonist after a CA of 13 years, no further increase in FAH is observed and even a negative correlation may be shown [ 38 , 67 , 68 ]. In girls with CPP, menarche is predicted after an average of 12 to 18 months after the completion of treatment and may begin after a few months or be delayed as long as 2 years [ 58 , 69 ]. It is recommended that the discontinuation of GnRH agonist treatment be decided after providing information about the FAH and pubertal progression to the guardians and patients, as well as an achievement of appropriate BA or CA.…”
Section: Development Of Cpgsmentioning
confidence: 99%